Pengaruh Perpustakaan Sekolah Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Bahasa Indonesia di SMAN 1 Martapura - Oktariani Oktariani; Missriani Missriani; Yessi Fitriani (Journal on Education, 2023)
This study aims to describe and analyze the influence of the library on student learning outcomes in the Indonesian language subject at SMA Negeri 1 Martapura. This research is a quantitative study using the partial correlation method which was conducted at SMA Negeri 1 Martapura with a sample of 257 students. Data collection techniques using questionnaires and documentation. Instrument test using validity test and reliability test. Prerequisite analysis analysis used the normality test, linearity test, and multicollinearity test, and data were analyzed using descriptive data analysis techniques, t-test analysis, F-test analysis and analysis of the determinant coefficient test. The results showed: There is a significant influence of the library on student learning outcomes in the Indonesian language subject at SMA Negeri 1 Martapura. This is indicated by a significant value of 0.000 which is less than 0.05 so that Ho is rejected, meaning that it can be concluded that Ha is accepted. This means that there is a significant influence of the School Library on Student Learning Outcomes at SMA Negeri 1 Martapura.